Paisagem e patrimônio natural na percepção das populações tradicionais e da dinâmica costeira na praia do vai quem quer, Ilha de Cotijuba, Belém – Pa - SANTOS, Alessandro Ferreira dos (2023)
This article was organized from a vulnerability study of the coastline of the northern portion of the island of Cotijuba, with data about the physical processes that the environment is affected, infiltration and sedimentation. In this sense, the concepts of heritage and landscape the article intends to discuss the representation of the population of the island regarding the risks. It aims to discuss the concepts of natural, cultural and heritage landscape through perspectives of residents, such perspectives are associated with coastal dynamic processes, in addition to demonstrating how the population perceives coastal dynamic processes in the generation and modification of the landscape with different uses. and occupations. For this, the adopted methodology was based on bibliographical review; that address the use of geotechnology tools; added to the field activity for observation and survey of information from the study area through open conversations, which help the analysis of the perception of the residents in the recognition of the landscape and the different uses and occupations to understand how to register about the natural landscape, the coastal dynamics of the area to be studied where the phenomena of attraction and the removal of materials found on the beach and on the cliffs for the construction of walls and residences were reported. In view of this, it is noted that on the island of Cotijuba the landscape is perceived from the change in the coastline, the continuous retreat of the cliffs and a change in the profile of the local economy. The island of Cotijuba is subject to exposure, the landscape has been integrated with other uses, from bathing to the use of restaurants, leisure, and tourism. The natural features, which call the attention of the population, some of these elements such as rocks and sand are used for many purposes, from the construction of houses, architectural elements. The landscape is thus seen, integrated, and used as a resource for the population of Cotijuba.